2019
DOI: 10.1186/s12886-019-1140-z
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of inositol supplementation in preterm infants to prevent retinopathy of prematurity: a systematic review and meta-analysis

Abstract: Background Inositol supplementation has been linked to beneficial effects on reducing the incidence of retinopathy of prematurity (ROP); however, it’s controversial. The meta-analysis aimed to check out the efficacy and safety of inositol supplementation in preterm infants for preventing ROP. Methods We conducted searches through PubMed, EMBASE, Medline, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, ClinicalTrials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Despite many clinical trials evaluating the efficacy of INS in different settings, poor quality evidence is available on the safety of INS. A meta-analysis evaluating the safety and efficacy of inositol supplementation in preterm infants for the prevention of the prematurity retinopathy showed no effect on the study outcomes but an increase in mortality in babies younger than 32 weeks [64]. Furthermore, studies evaluating safety reported short-term outcomes; thus, long-term follow-up studies should be considered to obtain a better safety evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many clinical trials evaluating the efficacy of INS in different settings, poor quality evidence is available on the safety of INS. A meta-analysis evaluating the safety and efficacy of inositol supplementation in preterm infants for the prevention of the prematurity retinopathy showed no effect on the study outcomes but an increase in mortality in babies younger than 32 weeks [64]. Furthermore, studies evaluating safety reported short-term outcomes; thus, long-term follow-up studies should be considered to obtain a better safety evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 70 years, numerous clinical trials have failed to identify effective and safe therapeutic strategies for ROP [ 55 , 84 ]. Such trials have included applications of recombinant human IGF-1 (rhIGF-1) in combination with rhIGFBP-3 [ 85 ], anti-oxidant vitamin E [ 86 , 87 ], inositol [ 88 ] and ω-3 PUFAs [ 89 ].…”
Section: Current and Emerging Therapiesmentioning
confidence: 99%
“…A recently published large multicenter randomized clinical trial did not confirm these data, but it reported that inositol administration resulted in a high incidence of serious adverse events, including necrotizing enterocolitis, hypotension, intraventricular hemorrhage, systemic infection, and respiratory distress [91]. An additional metaanalysis confirmed no benefits of inositol supplementation, while, on the other hand, it reported a trend toward an increase in mortality [92].…”
Section: Inositolmentioning
confidence: 97%